Otimização do ponto de entupimento de filtro a frio de biodiesel de babaçu - Girardi, Julio Cezar (2019)
The growing demand for energy linked by modernization and industrialization, coupled with environmental concerns fueled by global warming and climate imbalances, increasingly pushing biofuel research. Among the main biofuels studied is biodiesel, which is derived from the transesterification of vegetable oils or animal fats, and which, because it presents benefits such as non-toxic, non-aromatic, non-sulfating, biodegradable and good lubrication. Despite the benefits of biodiesel to the environment, its properties as a fuel are still not ideal, presenting physical and chemical characteristics that, if not controlled, damage and decrease the performance of the engines, such as viscosity, specific mass, oxidative stability and cold filter plugging point. As a solution to these problems, studies using mixtures that can improve the characteristics of biodieses have been performed, these mixtures are diverse, the most common are with diesel, use of alcohols and other biodieses. This work proposes to apply a factorial design 23 in laboratory scale in order to optimize the antifreeze process of babassu biodiesel, using isoamyl alcohol, camphor and limonene. The biodiesel was be characterized, following technical standards, afterwards, the additive mixtures was be used following the proportions established by the factorial design, and then the freezing properties and other physicochemical properties was be evaluated. In this way, this work attempt to use the additives at the biodiesel to obtain better quality biodiesel, which can be used as biofuel, and to determine the optimum conditions for each proposed additive. This study was financed in part by the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior - Brasil (CAPES) - Finance Code 001.